2014
DOI: 10.1111/pbi.12162
|View full text |Cite
|
Sign up to set email alerts
|

Related to ABA‐Insensitive3(ABI3)/Viviparous1 and AtABI5 transcription factor coexpression in cotton enhances drought stress adaptation

Abstract: Drought tolerance is an important trait being pursued by the agbiotech industry. Abscisic acid (ABA) is a stress hormone that mediates a multitude of processes in growth and development, water use efficiency (WUE), and gene expression during seed development and in response to environmental stresses. Arabidopsis B3-domain transcription factor Related to ABA-Insensitive3 (ABI3)/Viviparous1 (namely, AtRAV2) and basic leucine zipper (bZIPs) AtABI5 or AtABF3 transactivated ABA- inducible promoter: GUS reporter exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 82 publications
7
62
0
1
Order By: Relevance
“…4B). These results, coupled with the phenotype of transgenic cotton (Gossypium hirsutum), suggested that RAV1 interacted physically with ABI5 to increase resistance to drought stress in plants (Mittal et al, 2014).…”
Section: Validating Novel Interactions In the Aba Signaling Networkmentioning
confidence: 96%
See 1 more Smart Citation
“…4B). These results, coupled with the phenotype of transgenic cotton (Gossypium hirsutum), suggested that RAV1 interacted physically with ABI5 to increase resistance to drought stress in plants (Mittal et al, 2014).…”
Section: Validating Novel Interactions In the Aba Signaling Networkmentioning
confidence: 96%
“…A recent study showed that RAV1 coexpression with ABI5 enhanced plant resistance to imposed drought stress (Mittal et al, 2014). Thus, BiFC assays were performed to validate the interaction between the proteins RAV1 and ABI5 in plant cells.…”
Section: Validating Novel Interactions In the Aba Signaling Networkmentioning
confidence: 99%
“…This was done using a two-tailed Student's t-test, assuming equal 286 variance except for ABA quantifictation, where a one-tailed t-test was used on grounds prior 287 work (Mittal et al 2014(Mittal et al , 2015 showed the test genotypes were drought tolerant/ABA 288 hypersensitive. 289…”
Section: Statistical Analysis 283mentioning
confidence: 99%
“…This observation is consistent 301 with prior results from greenhouse and field that the AtABI5 1-1-1 event has more extreme 302 phenotypic effects than AtABI5 13-4-1 for longer fiber lengths, larger leaf area, greater root 303 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 biomass, and higher WUE (Mittal et al, 2014(Mittal et al, , 2015. LA lower, but still detectable (inset arrow), 304 that endogenous stress response markers Responsive to ABA18 (GhRAB18), GhRAV, 325…”
Section: Characterization Of Transgene Protein Accumulation In Cottonmentioning
confidence: 99%
See 1 more Smart Citation